2019
DOI: 10.1177/0308518x19862580
|View full text |Cite
|
Sign up to set email alerts
|

Financialization and non-disposable women: Real estate, debt and labour in UK care homes

Abstract: This paper contributes to debates on financialization, neoliberalism and labour by investigating the ownership of UK care homes by investment funds. This form of financialized ownership has been driven by debt financing and the realization of value from property assets. Financialization has also been shaped by labour. First, the low status of the mostly female workforce enabled investor buy-outs. Second, growing financial pressures have been partly absorbed by the interactive labour of care. This reflects a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 48 publications
0
80
0
1
Order By: Relevance
“…This research sought to identify changing patterns of care home ownership and financing; to explore the implications for the built environment and access to good care; and to examine the potential risks associated with dominant business models. Industry data showed that private equity firms dominated large transactions in the 2000s (Horton, 2019). By the mid‐2010s, REITs had also come to play a remarkably important role – as creditors, developers, and landlords – according to reports from major care companies, specialist consultancies, and industry press.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research sought to identify changing patterns of care home ownership and financing; to explore the implications for the built environment and access to good care; and to examine the potential risks associated with dominant business models. Industry data showed that private equity firms dominated large transactions in the 2000s (Horton, 2019). By the mid‐2010s, REITs had also come to play a remarkably important role – as creditors, developers, and landlords – according to reports from major care companies, specialist consultancies, and industry press.…”
Section: Methodsmentioning
confidence: 99%
“…Such investors introduced risky, extractive business models – using high levels of debt to buy care homes and counting on a mass market of publicly funded residents. Private equity firms dominated large transactions of care companies in the 2000s and early 2010s, but their business models proved unsustainable and have since faced heavy losses (Horton, 2019). Newer entrants and their impacts also require scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, a broader move towards neoliberalism and continuing austerity politics have led to the withdrawal of public services in many countries (cf. England, 2010; Horton, 2019). The declining availability of publicly funded services and the introduction of market competition via new public management reforms have promoted a twofold privatisation of care: It has been reframed as families' private responsibility and subjected to a market logic.…”
Section: The Commodification Of Care and The Emergence Of Globalised mentioning
confidence: 99%
“…First, care services today include an industry, and the production of life is increasingly integrated in circuits of commodity production. Accumulation may be limited in the care industry, because it cannot be made productive beyond a certain point (Himmelweit, 2002;Horton, 2019), and because it cannot be easily sliced into tasks amenable to discrete transactions (Hoppania & Vaittinen, 2015). Yet, care has become a commodity sold in a market, has been financialised and organized along logics of efficiency.…”
Section: The Care Economybeyond Production and Reproductionmentioning
confidence: 99%
“…Yet, it also invariably involves an emotional commitment that cannot be reduced to a rationalist logic of wage earning for survival. Although care workers are paid low wages and squeezed to the limit in the name of efficiency, they often establish close relationships with the people they care for that lead them to put the needs of others before self interest (Horton, 2019). Care labour thus constitutes an anomalyit is connected labour by definition, creating an interdependence between carers and those cared for, but it is also done for instrumental reasons of earning an income.…”
Section: The Care Economybeyond Production and Reproductionmentioning
confidence: 99%